SOSIALISASI LITERASI KEUANGAN PADA HIMPUNAN MAHASISWA MANAJEMEN UNIVERSITAS NEGERI MAKASSAR - Annisa Paramaswary Aslam; Nurul Fadilah Aswar; Andi Citra Pratiwi; Syarif Saddam Rivanie; Ayu Kartini Parawansa (Rafandha Press, 2023)
The socialization targets involved in this activity were students who are members of the Himpunan Mahasiswa Manajemen Universitas Negeri Makassar (UNM). The participants took part in educational and outreach activities related to financial literacy in the community. The purpose of this activity was to provide knowledge and insight to the Himpunan Mahasiswa Manajemen Universitas Negeri Makassar (UNM) so that participants gain knowledge and insight regarding financial literacy. In addition, the participants also participated in the dialogue process carried out by the service team. There were 45 students who attended on January 13-14 2023 at the BT Building, UNM Faculty of Economics. The method used in this outreach activity is an analysis of partner needs, socialization of financial literacy, and the discussion and evaluation stages.